Archives of Bassarabia 1929. Year I. No. 1 from January-March 1929 (Confluenţe Bibliologice, 2022)
The article discusses the importance of the magazine Arhivele Bessarabiei from 1929, Year I. No. 1 (January-March), prestigious publication, with a distinguished scientific attitude, on the pages of which new information was published for historians, geographers, theologians, ethnologists, sociologists, bibliologists. In this issue of the magazine, the role of two essential sciences is highlighted: history and geography, a study is published regarding a statistic of Moldova from 1809.
Keywords: history of Bessarabia; Romanian science; Archives of Bessarabia Magazine